(untitled) (UUM Journal of Legal Studies, 2014)
This study will delve into the Malaysian legal framework for the protection of refugee children; their legal status under the law; and guarantee to their rights. It will first identify the general protection under various Malaysian statutes relevant to refugee children. Discussion will continue to emphasise on any adverse effect of the legal provisions on refugee children. This will then followed by analysing Malaysia’s international commitment and obligation relating to children in general with some reference to refugee children. Discussion will touch on the role and mandate of the United Nation’s High Commissioner for Refugee’s (UNHCR) office, to protect refugee, Malaysia’s commitment as a state party to the United Nation Convention on the Rights of the Child (UNCRC) and it’s refusal to ratify the 1951 Convention Relating to the Status of Refugee (CRSR). Other dimension of this paper is the highlight of the adverse effects of inconsistent domestic legal provisions on the enjoyment of rights by refugee children. Finding of this study will show the extent of protection offered to refugee children under domestic laws and the reasons why Malaysia should fulfill its international obligation towards refugee children and further effort that must be initiated to ensure compliance to protection under international law. Keywords: Refugee children, Malaysian law, rights of the child.